Gambaran Kepuasan Pasien di Puskesmas Boja 1 Kabupaten Semarang - Rahma, Lutfiana Nur; Desty, Rani Tiara (Universitas Ivet, 2023)
Satisfaction is a form of one's feelings obtained from the product or service received. In the field of Health, customers are patients, and they are considered as the main indicator in assessing service quality. Based on the preliminary study, there were complaints that were obtained from suggestion boxes, in person, or online that patients were dissatisfied with the services received, such as the unfriendly health center staff, inadequate facilities, and differences in service delivery to BPJS and non-BPJS users at the Boja Health Center. 1. The purpose of this study was to see an overview of patient satisfaction at the Boja 1 Health Center on existing complaints. This study used a descriptive observational study with a cross-sectional design. The method used was purposive sampling by determining respondents who had conducted an examination at the Boja 1 Health Center. The results of this study using 9 variables that could affect patient satisfaction were that more than half of the respondents were satisfied with the services provided by the Boja 1 Health Center. However, there was an error. one variable that patients are still dissatisfied with is the advertising or promotion variable promised by the Puskesmas. With that it is necessary to make improvements to increase patient satisfaction so that the services provided can be optimal and support the service quality of the Boja 1 Health Center.